Kajian Formula Pupuk Organik, Anorganik dan Pupuk Hayati Untuk Meningkatkan Sifat Kimia Tanah Serta Hasil Bayam Cabut (Amaranthus Spp. L.) Pada Inceptisol - SUPADMA, A.A. NYOMAN; DANA, I MADE; ARTHAGAMA, I DEWA MADE (Agrotrop : Journal on Agriculture Science; Vol 12 No 1 (2022), 2022)
Study of Organic, Inorganic and Biofertilizer Formulas to Improve Some Soil Chemical Properties and Improve Yields of Spinach ( Amaranthus Spp . L) on Inceptisol . The aims of experiment to find the best and environmentally fertilizer formula to improve the yield of spinach and improve some properties soil chemistry. This research was a pot experiment in a green house conducted in Tabanan. Using a nested design two factors, consisting of 5 formulas combination of organic, inorganic and Biofertilizers, and 3 types of population of spinach plants per pot. The fertilizer formula are: F0 control), F1 (3 ton compos + 350 kg Urea + 2 % Biofertilizer), F2 (6 ton compos + 300 kg Urea + 4 % Biofertilizer), F3 = (9 ton + 250 kg Urea + 6 % Biofertilizer), F4 (12 ton + 200 kg Urea + 8 % Biofertilizer) per hektar, and population factors consist of: P1 = 4 plant, P2 = 8 plant, P3 = 12 plant per pot.  Each treatment was repeated 3 times so 45 experiment pots were needed. The parameters observed were: maximum plant height (cm), fresh plant weight at harvest, oven dry plant weight, soil pH, C-organic and soil CEC at harvest. The observational data were analyzed statistically, tested for variance to determine the effect of the treatment being tried. If significant effect is continued with the Duncans test of 5%. The results showed that the initial soil analysis showed low C-organic soil content, low total N-soil, low soil pH (6.3), and low soil CEC. The highest spinach plant height was achieved by F2P1 treatment of 25 cm, followed by F2P2 resulting in plant height of 23 cm. However, the highest fresh weight of full spinach is harvested at F2P2 treatment with a weight of 154 g per pot. Likewise, the best change in soil chemical properties was obtained in the F2P2 treatment.